1991
DOI: 10.1111/j.1346-8138.1991.tb03119.x
|View full text |Cite
|
Sign up to set email alerts
|

Acneiform Eruption Induced by Lithium Carbonate

Abstract: A 26-year-old female developed a severe acneiform eruption on her face, chest and back soon after she started taking lithium carbonate for psychosis. Histopathological examination revealed it to be folliculitis, rather than true acne. The eruption continued for six months but was resolved three months after discontinuing the drug. It has not reappeared in the following 3 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
3

Year Published

1997
1997
2011
2011

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 16 publications
0
7
0
3
Order By: Relevance
“…Halogenated aromatic compounds may cause chloracne (8), and exogenous factors, such as radiation, have also been implicated. Psychotropic medication, such as lithium (9), and, fairly recently, epidermal growth factor receptor inhibitors, such as cetuximab (10), are well-known causes of folliculitic reaction pattern, of which many cases display folliculitis with an infiltrate of neutrophils rather than true acne. Standard acne treatments can be employed without discontinuing the essential medications.…”
Section: Discussionmentioning
confidence: 99%
“…Halogenated aromatic compounds may cause chloracne (8), and exogenous factors, such as radiation, have also been implicated. Psychotropic medication, such as lithium (9), and, fairly recently, epidermal growth factor receptor inhibitors, such as cetuximab (10), are well-known causes of folliculitic reaction pattern, of which many cases display folliculitis with an infiltrate of neutrophils rather than true acne. Standard acne treatments can be employed without discontinuing the essential medications.…”
Section: Discussionmentioning
confidence: 99%
“…The typical acneiform eruption is characterized by a monomorphic papulopustular eruption on the trunk and extremities, without comedones or cysts, and sparing the face. 21,25 Nevertheless, some authors have also described cases with cysts and comedones. 26 Patients with a past or family history of acne are more predisposed to the development of an eruption.…”
Section: Acne and Acneiform Eruptionmentioning
confidence: 99%
“…60 In vitro studies of cultures of normal human skin with lithium have demonstrated the direct role of lithium in epidermal hyperproliferation, leading to the modification of epidermal barrier function by the production of intercellular edema and vacuolar alteration with the formation of small cavities in the upper dermis. 61 Patients with a positive family history for psoriasis should be carefully evaluated for the potential Table 1 Classification of dermatologic manifestations of lithium therapy Inflammatory disorders [36][37][38][39][40][41][42]95,[127][128][129][130]144,146,148,156 Psoriasis and pustular psoriasiform eruption, erythema multiforme, exfoliative dermatitis, fixed drug eruption, maculopapular eruption, eczematous reaction, seborrheic dermatitis Disorders of sebaceous/apocrine glands 21,25,[99][100][101] Acne and acneiform eruption, hidradenitis suppurativa Disorders of the hair and nails 46,68,[77][78][79]92,93,97,98 Alopecia, folliculitis, onychomadesis, nail dystrophy, nail discoloration Mucosal lesions [102][103][104][105]107,109,143 Geographic tongue, lichenoid stomatitis, oral mucosal ulcerations, vaginal ulcerations Keratinization disorders…”
Section: Psoriasismentioning
confidence: 99%
“…Acneiform eruptions are characterized by papules and pustules on the face, chest and upper back. Acneiform eruptions have been reported with lithium, 132 amineptine, 133–135 chlorpromazine 136 and maprotiline 137 . Diagnosis is reached clinically, and drug discontinuation, although not necessary, leads to improvement.…”
Section: Other Adverse Cutaneous Reactionsmentioning
confidence: 99%